1972
DOI: 10.1017/s0022112072002502
|View full text |Cite
|
Sign up to set email alerts
|

Effects of spanwise rotation on the structure of two-dimensional fully developed turbulent channel flow

Abstract: Experiments on fully developed turbulent flow in a channel which is rotating at a steady rate about a spanwise axis are described. The Coriolis force components in the region of two-dimensional mean flow affect both local and global stability. Three stability-related phenomena were observed or inferred: (i) the reduction (increase) of the rate of wall-layer streak bursting in locally stabilized (destabilized) wall layers; (ii) the total suppression of transition to turbulence in a stabilized layer; (iii) the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

47
232
3

Year Published

1989
1989
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 450 publications
(282 citation statements)
references
References 9 publications
47
232
3
Order By: Relevance
“…We will consider the experimental test case of Johnston, Halleen and Lezius (1972) for a Reynolds number Re = 11,500 and a rotation number Ro = 0.21 (here, Re = UoH/v and Ro = flH/Uo where UO is the bulk mean velocity). In Figure 5(a) the prediction for the mean velocity profile obtained from the SSG second-order closure by Speziale, So and Younis (1992) is compared with the experimental data of Johnston, Halleen and Lezius (1972). The computations were done using law of the wall boundary conditions.…”
Section: Illustrative Examplesmentioning
confidence: 99%
“…We will consider the experimental test case of Johnston, Halleen and Lezius (1972) for a Reynolds number Re = 11,500 and a rotation number Ro = 0.21 (here, Re = UoH/v and Ro = flH/Uo where UO is the bulk mean velocity). In Figure 5(a) the prediction for the mean velocity profile obtained from the SSG second-order closure by Speziale, So and Younis (1992) is compared with the experimental data of Johnston, Halleen and Lezius (1972). The computations were done using law of the wall boundary conditions.…”
Section: Illustrative Examplesmentioning
confidence: 99%
“…According to Xun et al [14], the effects of the Coriolis forces on the resolved turbulent stresses and TKE can be further studied using their transport equations. As revealed in the experimental study of Johnston et al [23] and DNS study of Kristoffersen and Andersson [35], the production terms in the transport equations of the resolved turbulent stresses TABLE 4.1: Production terms due to the mean turbulent shear (P ij ) and rotation (G ij ) stresses for a fullydeveloped rotating plane channel flow.…”
Section: Rotation Effect On the Resolved Turbulent Stressesmentioning
confidence: 96%
“…The Among the studies of turbulent channel flows subjected to these three types of system rotations, the spanwise rotating turbulent channel flows have been studied extensively through experiments [23,24] and numerical simulations [14,[25][26][27][28][29][30][31][32][33][34][35][36][37]. It is reported that as the rotation number increases, turbulence is gradually enhanced on the pressure side and reduced on the suction side, further resulting in asymmetric distributions in the mean flow and Reynolds stresses [14,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. At the same time, large-scale roll cells come forth as a result of the Taylor-G枚rtler (T-G) instability [14,23,25,35].…”
Section: Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…While the influence of the rotation of the reference frame on small scale turbulence is negligible in geophysical flow situations, this is not true for many engineering devices (Johnston et al 1972, Watmuff et al 1985. Also, it is not clear that rotation does not influence the large scale eddies.…”
Section: Influence Of Rotation On the Length Scalementioning
confidence: 99%